Bound State Operators and Wedge-Locality in Integrable Quantum Field Theories - Tanimoto, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We consider scalar two-dimensional quantum field theories with a factorizing S-matrix which has poles in the physical strip. In our previous work, we introduced the bound state operators and constructed candidate operators for observables in wedges. Under some additional assumptions on the S-matrix, we show that, in order to obtain their strong commutativity, it is enough to prove the essential self-adjointness of the sum of the left and right bound state operators. This essential self-adjointness is shown up to the two-particle component.